SEEING DOUBLE OLD AND NEW: OBSERVATIONS AND LIGHTCURVE ANALYSIS AT THE PALMER DIVIDE OBSERVATORY OF SIX BINARY ASTEROIDS - Warner, Brian D. (Minor Planet Bull, 2013)
Results of the analysis of lightcurves of six binary asteroids obtained at the Palmer Divide Observatory are reported. Of the six, three were previously known to be binary: 9069 Hovland, (26471) 2000 AS152, and 1994 XD. The remaining three are new confirmed or probable binary discoveries made at PDO: 2047 Smetana, (5646) 1990 TR, and (52316) 1992 BD.